Determinants of Capital Structure and their effect on the financing behaviour of Small Libyan Enterprises "An Empirical Study" - محمد , ميادة عبد الله; الكزة, عبد السلام أحمد; الفضلي, خالد زيدان (Scientific Journal of University of Benghazi, 2023)
This study aims to identify the determents of capital structure represented in the independent variables: project size, fixed assets, profitability, growth and their impact on the financing behaviour of the small Libyan enterprises measured by: total debt, long-term debt, short-term debt. The study sample consists of 31 small firms, and the data is analysed for the period 2015-2017, using statistical tools of correlation coefficient, regression, and variance analysis. The results of the study shows an effect of the characteristics of enterprises on the capital structure (total debt and short-term debt), and the study concluded that both the firm size and fixed assets have the most impact on the total debt, and that the firm size has a direct effect on short-term debt. Fixed assets have a direct effect on long-term debt. Moreover, the study concluded that the Pecking-order theory is the most among the capital structure theories to interpret and explain the financing behavior of the Libyan small enterprises.